The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevapplied.13.034053
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Field Dependence of the Anomalous Hall Effect in Ta/TbFeCo

Abstract: Experimental studies of anomalous Hall effect are performed for thin filmed Ta/TbFeCo in a wide range of temperatures and magnetic fields up to 3 T. While far from the compensation temperature (T M =277 K) the field dependence has a conventional shape of a single hysteresis loop, just below the compensation point the dependence is anomalous having the shape of a triple hysteresis. To understand this behavior, we experimentally reveal the magnetic phase diagram and theoretically analyze it in terms of spinreori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Note that this line is located to the right of the magnetization compensation point T M due to the influence of the anisotropy of the rare-earth sublattice. Note, that tricritical point P may located to the left from the compensation due to modifying the surface of the ferrimagnetic by the heavy metal film such as Ta [18]. The line RP transforms into an R P due to the exchange surface anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this line is located to the right of the magnetization compensation point T M due to the influence of the anisotropy of the rare-earth sublattice. Note, that tricritical point P may located to the left from the compensation due to modifying the surface of the ferrimagnetic by the heavy metal film such as Ta [18]. The line RP transforms into an R P due to the exchange surface anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, in the GdFeCo ferrimagnet, triple hysteresis loops are observed above the magnetization compensation temperature [14]. At the same time, experiments with TbFeCo with Ta capping layer [18] show that triple loops can appear to the left of the compensation point. To explain this anomalous hysteresis loop, theoretical models [19] were constructed, in which the interplay of the surface anisotropy, and anisotropies of both sublattices led to a modification of the phase diagrams.…”
Section: Introductionmentioning
confidence: 92%
“…[35,36] Furthermore, we assume that the anisotropy is completely dominated by the Gd sublattice, as was claimed earlier in the case of RE-TM alloys and multilayers. [45][46][47][48] More specifically, this means we replace M(T) by M Gd (T) in Equation ( 1) and let only M Gd (T) contribute to the anisotropy energy. The latter assumption, together with the Callen-Callen power law taking n = 3, will greatly reduce the anisotropy field barrier, providing the necessary "kick-start" to the precessional switching process.…”
Section: Magnetization Reversal Based On Llb Formalismmentioning
confidence: 99%
“…Very rich and interesting magnetization dynamics [13,14], in terms of fundamental and applied * zvezdin.ka@phystech.edu physics, is observed in these materials near the points of compensation of magnetization and angular momentum. Moreover, by manipulating the temperature of the ferrimagnet near the compensation points, outstanding magnetization switching characteristics can be obtained [15][16][17]. It has been shown that the electrical current can be an efficient approach to magnetization switching [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%